Peranan Komunitas Sel sebagai Kegiatan Misi dalam Meningkatkan Pertumbuhan Jemaat - Vriska Friyanti; Timotius Sukarna (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This paper discusses Christ wanting His church to have firm trust/faith in Him. A church that has true knowledge of Him, remains true to the truth of the Bible, and grows in love for God and fellow human beings. A church that increasingly increases its personal relationship with God and is brave in assuming responsibility and church service. This paper analyzes how the existence of cell groups greatly contributes and influences a person's spiritual growth, especially in terms of maturing congregation members to participate in ministry. In cell groups there is two-way communication, there is interaction in it, which is different from sermons which are only one-way. In a group, all members of the congregation have more opportunities to study the Bible than in worship on Sundays which only involve listening. At the discussion stage, in the cell group there is two-way communication, there is interaction in it, which is different from sermons which are only one-way. In a group, all members of the congregation have more opportunities to study the Bible than in worship on Sundays which only involve listening.